Arginine Vasopressin-Independent Mechanism of Impaired Water Excretion in a Patient with Sarcoidosis Complicated by Central Diabetes Insipidus and Glucocorticoid Deficiency - Katsunobu Yoshioka; Nagaaki Tanaka; Keiko Yamagami; Takeshi Inoue; Masayuki Hosoi (Case Reports in Medicine)
A 28-year-old man was admitted to our hospital because of reduced livido and increased fatigability. Four months before admission, he noticed polyuria, which was gradually relieved by admission. Magnetic resonance imaging revealed enhancing lesion centrally in the pituitary stalk. Biopsy from the skin revealed noncaseating granuloma composed of epithelioid cells, and a diagnosis of sarcoidosis was made. Although plasma arginine vasopressin (AVP) was undetectable after administration of hypertonic saline, urinary output was within normal range (1.5 to 2.2 L/day). The urine osmolality became above plasma levels during the hypertonic saline test. Hormonal provocative tests revealed partial glucocorticoid deficiency. Soon after the glucocorticoid therapy was begun, moderate polyuria (from 3.5–4.0 liters daily) occurred. At this time, plasma AVP was undetectable, and urine osmolality was consistently below plasma levels during the hypertonic saline test. In conclusion, we showed in human study that masked diabetes insipidus could be mediated by AVP-independent mechanisms.